Structural Modeling and XRD Analysis of (PVA:LiOH)–Fe₃O₄ Composite Electrolyte for Supercapacitor Applications - Rahmawati Munir; Dadan Hamdani; Darnah Andi Nohe; Rahmiati Munir; Igor Levi Satriani; Siti Fatimah; Sahara Hamas Intifadhah (Progressive Physics Journal, 2026)
The development of supercapacitors requires electrolyte membranes with high ionic conductivity and magnetic properties to enhance energy storage performance. This study aims to visualize the crystal structure and simulate the X-ray diffraction (XRD) patterns of the (PVA:LiOH)–Fe₃O₄ composite electrolyte membrane using the VESTA software as the basis for analyzing its potential application in magnetic supercapacitors. The material was synthesized through the sol–gel method, with PVA serving as the polymer matrix, LiOH as the lithium ion source, and Fe₃O₄ as the magnetic filler. Crystal structure characterization was performed using XRD measurements, followed by modeling of the Fe₃O₄ and LiOH crystalline phases based on reference CIF data, while PVA was represented as an amorphous matrix. The simulated multiphase XRD pattern was validated against experimental data to confirm the agreement between diffraction peaks and crystal phases. The three-dimensional supercell visualization revealed the spatial distribution of Fe₃O₄ and LiOH particles within the polymer matrix. Electrical measurements demonstrated an increase in ionic conductivity from the order of 10⁻⁴ S/cm in PVA:LiOH membranes to 10⁻³ S/cm after Fe₃O₄ incorporation. This enhancement is attributed to the formation of more efficient ion transport pathways resulting from the interaction between the magnetic filler and the polymer matrix. The simulated XRD results reinforce the correlation between crystal structure, phase distribution, and ionic conductivity performance. These findings suggest that the (PVA:LiOH)–Fe₃O₄ composite possesses strong potential as an electrolyte membrane for magnetic supercapacitors, opening opportunities for developing materials with combined electrochemical and magnetic properties to improve energy storage efficiency.